Review Article: Lake and breach hazard assessment for moraine-dammed lakes: an example from the Cordillera Blanca (Peru) - Emmer, Adam (2013)
Original abstract: Glacial lake outburst floods (GLOFs) and related debris flows represent a significant threat in high mountainous areas across the globe. It is necessary to quantify this threat so as to mitigate their catastrophic effects. Complete GLOF hazard assessment incorporates two phases: the probability of water release from a given glacial lake is estimated through lake and breach hazard assessment while the endangered areas are identified during downstream hazard assessment. This paper outlines a number of methods of lake and breach hazard assessment, which can be grouped into three categories: qualitative, of which we outline eight; semi-quantitative, of which we outline two; and quantitative, of which we outline three. It is considered that five groups of critical parameters are essential for an accurate regionally focused hazard assessment method for moraine-dammed lakes in the Cordillera Blanca. These comprise the possibility of dynamic slope movements into the lake, the possibility of a flood wave from a lake situated upstream, the possibility of dam rupture following a large earthquake, the size of the dam freeboard (or ratio of dam freeboard), and a distinction between natural dams and those with remedial work. It is shown that none of the summarised methods uses all these criteria with, at most, three of the five considered by the outlined methods. A number of these methods were used on six selected moraine-dammed lakes in the Cordillera Blanca: lakes Quitacocha, Checquiacocha, Palcacocha, Llaca, Rajucolta, and Tararhua. The results have been compared and show that each method has certain advantages and disadvantages when used in this region. These methods demonstrate that the most hazardous lake is Lake Palcacocha.